Study on Fracture and Stress Evolution Characteristics of Ultra-Thick Hard Sandstone Roof in the Fully Mechanized Mining Face with Large Mining Height: A Case Study of Xiaojihan Coal Mine in Western China - Feng Ju; Meng Xiao; Zequan He; Pai Ning; Peng Huang (Advances in Civil Engineering)
Ultra-thick hard sandstone roofs present high thickness, poor delamination, and wide caving range. The strata pressure of the working face during actual mining increases, having a significant influence on the safe mining of the working face. Especially, in the mining areas of western China, the fully mechanized mining faces with high mining height and high-strength mining are more prominent. Understanding the fractures and stress evolution characteristics of the ultra-thick hard sandstone roof during actual mining is of high significance to control the dynamic pressure on the working face. In this paper, the typical ultra-thick hard sandstone roof of the Xiaojihan coal mine was taken as an example. The structural and chemical composition characteristics were analyzed. Besides, the fracture characteristics of ultra-thick hard roof during the working face mining were analyzed. Moreover, the fracture structure consistency was verified through physical simulation and a field measurement method. Finally, the stress evolution laws in the ultra-thick hard sandstone roof fracture were studied through numerical simulation. The findings demonstrated that (1) the ultra-thick hard sandstone roof was composed of inlaid coarse minerals, which had compact structure, while the Protodyakonov hardness reached up to 3.07; (2) under the high-strength mining condition of fully mechanized mining face with large mining height, the ultra-thick hard sandstone roof had the characteristics of brittle fracture, with a caving span of 12 m; (3) under the high-strength mining condition of fully mechanized mining face with large mining height, the ultra-thick hard sandstone roof followed the stress evolution laws that were more sensitive to the neighboring goaf. Therefore, it was necessary to reduce the fracture span or layering of ultra-thick hard sandstone roof through the manual intervention method adoption or increase either the strength of coal pillar or supporting body, to resist the impact generated during ultra-thick hard sandstone roof fracture.